Challenge in challenging times: a case report of ruptured isthmic ectopic pregnancy in an asymptomatic COVID-19 positive patient - Gahlot, Ankita; Raval, Atri; Yadav, Bindoo; Saxena, Swarnima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Emergency surgical management of patients who are COVID-19 positive is extremely challenging for the treating doctors as there is a need to keep the balance between delivering optimal medical care to the patient, preventing spread to others and protecting ourselves. COVID-19 manifestations in pregnant women are similar to non-pregnant patients. The patient may be asymptomatic or may present with symptoms like cough, cold, fever and shortness of breath. In obstetric emergencies like ruptured ectopic pregnancy, when a patient presents in casualty with history of amenorrhea, pain abdomen and features of shock, main priority for the clinician is to stabilize them and treat the underlying cause so as to save their life. We report the emergency management of a hemodynamically unstable ruptured ectopic pregnancy at 9 weeks of gestation in a COVID-19 positive patient. It was stressful for the treating doctors because of high infectivity of the disease, scarcity of resources during the pandemic and precarious condition of the patient.